Tumbuka Folktales : Moral and Didactic Lessons from Malawi - Shaŵa, Lester Brian (Book collections on Project MUSE., 2013)
Tumbuka folktales are on the verge of extinction. If not recorded now, the loss would not only be the amusement they provide but chiefly lessons inherent. On the surface, they are simple narratives, however, subtly they evoke serious moral lessons that are very applicable to our everyday life today. This folklore collection is based on field research conducted by the authors in Citumbuka speaking areas of Mzimba and Rumphi districts in Nothern Malawi.